Застосування перетворення Келі і методу інтегральних рівнянь для чисельного розв’язування лінійної осесиметричної задачі слошингу - Даців, Г.П.; Хапко, Р.С. (Видавничий дім "Академперіодика" НАН України, 2008)
We consider an evolution problem on free boundary arising in the linear sloshing. A numerical solution is realized through the Cayley transformation with respect to time and the integral equation method with respect to spatial variables. Taking into account the axial symmetry, the sequence of one-dimensional integral equations of the second kind is obtained. The full discretization is performed by the Nystr¨om method with non-linear mesh grading transformation.